An Examination of the Influence of Exposure to Disciplinary Segregation on Recidivism. (April 2020) - Butler, H. Daniel; Steiner, Benjamin; Makarios, Matthew D.; Travis, Lawrence F.
Inmates who violate prison rules and regulations may be confined in disciplinary segregation as a punishment, which includes a loss of privileges and reduced opportunities to socialize and participate in prison programming. Few studies have explored the relationship between confinement in disciplinary segregation and recidivism. In this study, data collected from offenders released to postrelease supervision in Ohio are used to examine how various types of exposure to confinement in disciplinary segregation influence the odds of recidivism. In addition, confinement in disciplinary segregation in the months preceding release from prison is examined by use of difference of means tests. We found that confinement in disciplinary segregation and the timing of confinement prior to release are associated with increased odds of recidivism.